EVALUATION OF TREATMENT OUTCOMES OF PRIMARY KNEE OSTEOARTHRITIS USING AUTOLOGOUS PLATELET-RICH PLASMA INJECTION THERAPY AT MILITARY HOSPITAL 91 (Vietnam Journal of Community Medicine, 2026)
Objectives: To evaluate the treatment outcomes of primary knee osteoarthritis using autologous platelet-rich plasma (PRP) injection therapy at Military Hospital 91.Subjects and methods: This was an interventional, before-and-after study without a control group, including 66 patients diagnosed with primary knee osteoarthritis at Military Hospital 91.Results: The age group 60–69 years accounted for the highest proportion (42.42%), with females representing 57.6%. Most patients had stage 2 or 3 primary knee osteoarthritis. After 6 months of treatment, mechanical pain persisted in 74.2% of patients, inflammatory pain in 3.0%, and morning stiffness decreased to 9.1%. The mean VAS pain score before treatment was 6.39 ± 1.15; after 3 and 6 months it decreased to 2.77 ± 1.58 and 1.98 ± 1.57, respectively. The proportion of patients without joint effusion increased to 78.8%, while those with severe effusion decreased from 7.6% to 0%. The rate of synovitis declined from 36,4% at baseline to 13.6% after 3 months and 3.0% after 6 months. The mean cartilage thickness measured by ultrasound after 3 and 6 months, respectively, was as follows: lateral femoral condyle cartilage 1.93 ± 0.44 mm and 2.03 ± 0.43 mm; intercondylar cartilage 2.35 ± 0.29 mm and 2.41 ± 0.32 mm; medial femoral condyle cartilage 1.73 ± 0.42 mm and 1.80 ± 0.45 mm. These differences were statistically significant (p < 0.05).Conclusions: Autologous platelet-rich plasma injection therapy is effective in improving symptoms of primary knee osteoarthritis, including reduction of inflammatory and mechanical pain as well as morning stiffness. Ultrasound findings showed decreased synovial inflammation and increased cartilage thickness.
Keywords: Knee osteoarthritis, platelet-rich plasma (PRP), knee ultrasound.